2009
DOI: 10.1111/j.1600-0404.1990.tb00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmoplegic migraine: diagnostic criteria, incidence of hospitalization and possible etiology

Abstract: Charts from patients admitted from April 1976 to March 1986 to the departments of neurology, neurosurgery, ophthalmology and pediatrics serving a population of 615,000 inhabitants in Copenhagen County were surveyed. We then examined patients with coexisting headache and ophthalmoplegia at follow‐up. Many diseases may mimic a single attack of ophthalmoplegic migraine. We found 4 cases of ophthalmoplegic migraine, i.e. an annual incidence of 0.7 per million inhabitants. We added another 4 cases from the same are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 13 publications
0
27
0
3
Order By: Relevance
“…The prevalence is estimated to be 0.7 per million [5–7]. Hansen et al [5] reviewed the charts of patients admitted from April 1976 to March 1986 to the departments of neurology, neurosurgery, ophthalmology and pediatrics, serving a population of 615,000 inhabitants in Copenhagen County. They then examined patients with coexisting headache and ophthalmoplegia at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence is estimated to be 0.7 per million [5–7]. Hansen et al [5] reviewed the charts of patients admitted from April 1976 to March 1986 to the departments of neurology, neurosurgery, ophthalmology and pediatrics, serving a population of 615,000 inhabitants in Copenhagen County. They then examined patients with coexisting headache and ophthalmoplegia at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmoplegic migraine is a very rare condition, previously thought to represent a variant of migraine, but the headaches in ophthalmoplegic migraine often do not fulfi ll formal migraine criteria. 5 Mark et al reported a patient with ophthalmoplegic migraine in whom enhancement of the cisternal segment of the oculomotor nerve was seen on contrast-enhanced MRI. 6 They have suggested that the presence of oculomotor changes on MRI should be required for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…안근 마비성 편두통의 발생률은 정확히 알려져 있지 않지만, Hansen은 매년 백만명 당 0.7명 정도로 추정하고 있으며 편두통과는 달리 남성에 더 호 발 한다고 보고하였다 2,14) . 안근마비성 편두통의 발생 기전은 정확하게 밝혀지지 않았으며 신경 학적 검사나 영상검사를 통해 다른 기질적인 질 환을 배제한 후에 진단할 수 있다 2,12,20) .…”
unclassified
“…안근 마비성 편두통은 모든 연령에서 발생할 수 있지 만 주로 10세 이전에 발생하고 성인이 된 이후 에 발병하는 일은 드물다 12,13,25) . 주로 3번 뇌신경 마비를 가장 많이 동반하게 되고 4번 뇌신경이 나 6번 뇌신경도 침범될 수 있다고 알려져 있다 2,12,14,15,25) . …”
unclassified